Quantized output feedback stabilization for nonlinear discrete-time systems subject to saturating actuator - Song, Gongfei; Li, Tao; Li, Yuanlu; Lu, Junwei (Nonlinear dynamics, 2016)
The quantized output feedback stabilization problem for nonlinear discrete-time systems with saturating actuator is investigated. The nonlinearity is assumed to satisfy the local Lipschitz condition. Different from the previous results where the Lipschitz constant is predetermined, a more general case is considered, where the maximum admissible Lipschitz constant through convex optimization is obtained. In this framework, two kinds of quantizations are derived simultaneously: quantized control input and quantized output. Furthermore, sufficient conditions for the existence of static output feedback control laws are given. The desired controllers ensure that all the trajectories of the closed-loop system will converge to a minimal ellipsoid for every initial condition emanating from a large admissible domain. Finally, four illustrative examples are provided to show the effectiveness of the proposed approach.